The diagnostic value of multiparameter cardiovascular magnetic resonance for early detection of light-chain amyloidosis from hypertrophic cardiomyopathy patients - Yue, Xiuzheng; Yang, Lili; Wang, Rui; Chan, Queenie; Yang, Yanbing; Wu, Xiaohong; Ruan, Xiaowei; Zhang, Zhen; Wei, Yuping; Wang, Fang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac involvement of amyloidosis is more likely underdiagnosed or misdiagnosed. It is vital to identify early diseases of cardiac light-chain amyloidosis (AL CA) or suspected AL CA patients with atypical Late gadolinium enhancement (LGE) patterns from other cardiomyopathy patients. We aimed to investigate the left ventricular (LV) strain, native T1, extracellular volume (ECV), and LGE between all AL CA patients, hypertrophic cardiomyopathy patients (HCM), and healthy control subjects (HA). Moreover, we investigate the diagnostic value of multiparameter CMR for the early stage of AL CA patients from HCM patients. Methods: Thirty-eight AL CA patients, sixteen HCM patients, and seventeen HA people were prospectively recruited. All subjects were scan LGE imaging, Cine images, and T1 mapping on a 3T scanner. According to their clinical and biochemical markers, all patients were classified as Mayo I/II and Mayo IIIa/IIIb. Univariable and multivariable logistic regression models were utilized to ﬁgure out independent predictors of early-stage AL CA from HCM patients. Receiver operator characteristic (ROC) curve analysis and Youden’s test were done to determine the accuracy of multiparameter CMR in diagnosing Mayo I/II of AL CA patients and establish a cutoff value. Results: For Mayo I/II stage AL CA patients, the global longitudinal strain (GLS) absolute value (11.9±3.0 vs. 9.5±1.8, P<0.001), the global circumferential strain (GCS) absolute value (19.0 ±3.6 vs. 9.5±1.8, P<0.001) were significantly higher than HCM patients. Especially, ECV values (37.8±5.7% vs. 31.3±2.5%, P<0.0001) were higher than that of HCM patients. ROC curve analysis and Youden’s test were used on GCS, GLS, and ECV for differentiating between Mayo IAL amyloidosis and HCM patients. respectively. The combined diagnostic performance of GLS, GCS and ECV mapping can well distinguish Mayo IAL amyloidosis patients from hypertrophic cardiomyopathy (AUC = 0.969, Youden index=0.813). Conclusions: For early-stage AL CA patients with atypical LGE, which have similar imaging symptoms to HCM patients, The combination of GCS, GLS and ECV could highly accurately differentiate early stage AL CA from controls from HCM patients, which could be as a novel approach to studying CMR characteristics in patients with earlier stage CA With multiple follow-ups.